BOARDING SCHOOL MANAGEMENT IN QUALITY IMPROVEMENT AT ISLAMIC STATE HIGH SCHOOL (MAN 4) BANJARMASIN INDONESIA - Suraijiah, Suraijiah; Madani, Akhmad (Faculty of Education Universitas Negeri Malang, 2022)
Boarding School Management in Education Quality Development at MAN 4 Banjar Kalimantan is a research that focuses on planning, organizing, implementing and monitoring boarding school programs in developing the quality of education, in developing the quality of education at MAN 4 Banjar South Kalimantan. This type of research is a field research using a qualitative approach. The data collection techniques used the method of observation, interviews and documentation. The results of the study illustrate that the implementation of boarding school management at MAN 4 Banjar South Kalimantan has been carried out well as evidenced by the existence of planning such as administration and preparation of activities that have been listed in the hostel guide book, organizing boarding schools with separate structures and already having tasks according to the head's decree. madrasas, implementation in accordance with dormitory guidelines, monitoring of boarding school program activities in the development of the quality of education is also carried out on three aspects of development, namely: religious, boarding and linguistic.